Three‐dimensional structure and cyanobacterial activity within a desert biological soil crust. (27th April 2015) - Raanan, Hagai; Felde, Vincent J. M. N. L.; Peth, Stephan; Drahorad, Sylvie; Ionescu, Danny; Eshkol, Gil; Treves, Haim; Felix‐Henningsen, Peter; Berkowicz, Simon M.; Keren, Nir; Horn, Rainer; Hagemann, Martin; et al.
Summary: Desert biological soil crusts (BSCs) are formed by adhesion of soil particles to polysaccharides excreted by filamentous cyanobacteria, the pioneers and main producers in this habitat. Biological soil crust destruction is a central factor leading to land degradation and desertification. We study the effect of BSC structure on cyanobacterial activity. Micro‐scale structural analysis using X‐ray microtomography revealed a vesiculated layer 1.5–2.5 mm beneath the surface in close proximity to the cyanobacterial location. Light profiles showed attenuation with depth of 1%–5% of surface light within 1 mm but also revealed the presence of 'light pockets', coinciding with the vesiculated layer, where the irradiance was 10‐fold higher than adjacent crust parts at the same depth. Maximal photosynthetic activity, examined by O2 concentration profiles, was observed 1 mm beneath the surface and another peak in association with the 'light pockets'. Thus, photosynthetic activity may not be visible to currently used remote sensing techniques, suggesting that BSCs' contribution to terrestrial productivity is underestimated. Exposure to irradiance higher than 10% full sunlight diminished chlorophyll fluorescence, whereas O2 evolution and CO2 uptake rose, indicating that fluorescence did not reflect cyanobacterial photosynthetic activity. Our data also indicate that although resistant to high illumination, the BSC‐inhabiting cyanobacteria function as 'low‐light adapted' organisms.